Content Marketing Training and Assistance to Micro Enterprises from Rumah Kreatif BUMN-Telkom Community in Malang Regency - Moch Fuad Nasvian; Radityo Widiatmojo; Aditya Dwi Putra Bhakti; Zen Amirudin (Journal of Community Practice and Social Welfare, 2021)
The Covid-19 pandemic in Indonesia forces people to have different behaviours, both socially and economically. This epidemic has made Indonesians’ shopping behaviour change; online shopping and cashless transactions have increased rapidly. Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has left behind this consumer behaviour change. The BUMN Creative House (RKB) is a government effort to improve MSMEs’ quality in products, marketing, and funding. Regularly, RKB provides its members with training, workshop but cannot afford to assist their new knowledge. Telkom Indonesia manages the RKB in Malang Regency. This service activity is in the form of training and mentoring for MSMEs who are also partners of the RKB. The training lasts for three weeks, with tiered materials about content marketing and one month of assistance after the last session training to deepen their skills to help MSMEs setup their new digital marketing technique and deepen their skills. From this program, we found that (1) MSMEs digital literacy is varied depending on their age; (2) Greater Malang MSMEs is slow to adapt in new digital marketing technique, they even scared to try it, because even after one month of assistance, only 3 out of 15 businesses can advertise on the Facebook Platform.